Chronic Timing and pharmacological support in the surgical treatment of multiple perianal fistulas in Crohn’s Disease - Lorenzetti, R.; Gruppo, M.; Piatto, et al., G. (Acta Biomedica Atenei Parmensis, 2012)
Abstract. We present a case report on the management of a young woman affected by Crohn’s Disease ever since childhood, complicated by complex, multiple perianal fistulas.  In literature, there is increasing evidence to support the treatment of perianal fistulas using a combined association of medical and surgical strategies. In the case of our patient, the choice of surgery in association with pharmacological treatment was supported by the consideration of the fact that intervening during a quiescent phase of the disease, from the symptomatic, clinical-biohumoral and endoscopic standpoint, would have reduced the risk of complications and thus promoted healing.